Efektivitas Model Pembelajaran Kooperatif Tipe Think Talk Write (Ttw) Terhadap Kemampuan Komunikasi Matematika Siswa Kelas VIII MTs Negeri Godean - Risdiyati, Fety; Miyanti, Sri Endah; Sagita, Laela (Pendidikan Matematika Universitas PGRI Yogyakarta, 2016)
The research aims to determine the effectiveness of cooperative learning model type Think Talk Write (TTW) and type Think Pair Share (TPS) toward the mathematic communication skill students of grade 8th in MTs N Godean. This type of research is comparative descriptive which aplies Pretest Posttest Control Group Design. An instrument used in this study there are two kinds of the instruments learning and instruments data collection. An instrument consisting of learning implementation lesson plans and sheets of student activity, instruments gather data consists of broad observation, questionnaire, a test (pretest and posttest) and documentation. Analysis of data on research use t test some help software Ms. Excel 2010 and SPSS 20. The results of research pretest and posttest show that experiment class with cooperative model type Think Talk Write (TTW) and control class with cooperative model type Think Pair Share (TPS) normal distribution, both classes are homogenous and both classes have the same initial capability. The cooperative learning model type Think Talk Write (TTW) is same effective with cooperative learning model type Think Pair Share (TPS) toward the mathematic communication skill students. The level of effectiveness cooperative learning model type Think Talk Write (TTW) is 0,30 with medium category and the level of effectiveness cooperative learning model type Think Pair Share (TPS) is 0,28 with low category. Cooperative learning model type Think Talk Write (TTW) is same effective with cooperative learning model type Think Pair Share (TPS) because the students are individually active role in group discussions and there is the same syntax for these two models namely stage think.Keyword: Cooperative learning model type Think Talk Write (TTW), cooperative learning model type Think Pair Share (TPS), mathematic communication skill students.